Promoting Self-Regulated Learning of Reading Ability in University Students: EFL Lectures’ Perspective - Sakhi Herwiana; Oikurema Purwati; Syafiul Anam (ELITE JOURNAL, 2023)
Research that explored the SRL perspective on the reading ability of EFL lecturers in the English education department of Indonesian universities is under research. Thus, this study aims to observe EFL lecturers’ knowledge and implementation of SRL instructions in the classroom setting particularly in reading ability. Self-regulated learning and literacy skills are required for students to be mastered in 21st-century education as stated in the Independent Curriculum of 2022. Moreover, University students in the English education department are strongly recommended to gain knowledge of SRL strategies because they will be teachers in the future. SRL strategies can be adopted and transferable, they may lead to creating critical thinkers and autonomous learners as 21st-century skills. Therefore, implementing SRL strategies in the classroom can give advantages for preparing potential teachers. This study used a qualitative survey method. The findings revealed that participants are familiar with and agree that SRL can give a positive impact to get better academic achievement. Nevertheless, they are unaware that they use SRL instructions in teaching activities. They do not recognize that they involve cognitive and metacognitive strategies of SRL. Furthermore, they never use motivational strategies.Keywords: EFL classroom; perspective; reading ability; self-regulated learning.